Application of glass with atomic-scale precision network structure manufacturing characteristics, low forming area temperature and relatively high fracture toughness
By using glass materials with low alumina content and an all-electric melting furnace process, combined with precisely controlled temperature and testing methods, the problem of crystallization in high-alumina glass has been solved, enabling efficient production and energy-saving glass products with atomically precise network structures and high fracture toughness.
Patent Information
- Application Number
- CN202510532469.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-29
- Filing Date
- 2025-04-25
- Publication Date
- 2025-10-28
AI Technical Summary
In existing technologies, high-alumina glass is prone to crystallization during the production process, which leads to production difficulties and high energy consumption, making it difficult to achieve large-scale production and energy conservation.
By using glass materials with low alumina content, controlling the viscosity and crystallization temperature of the molten glass, and replacing natural gas heating with an all-electric furnace process, combined with a precisely controlled atmosphere furnace and a high-temperature viscosity tester, we ensure that the molten glass does not crystallize during the forming process, and employ a variety of forming processes.
It achieves an atomically precise network structure for glass products, low forming zone temperature and high fracture toughness, reduces the risk of crystallization, improves production safety and energy efficiency, reduces energy consumption and production costs.
Smart Images

Figure CN120841837A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the application of a glass material and its production equipment and methods, specifically to the technical field of glass applications with atomically precise network structure manufacturing characteristics, low forming zone temperature, and high fracture toughness.
[0002] This invention has a wide range of applications, including the following eight major industrial sectors:
[0003] 1. Including industrial applications in architectural glass;
[0004] 2. Industrial applications including the materials, design, and engineering construction of interior and exterior walls, floors, lobbies, and doors of glazed glass and composite materials, as well as special glazed glass decorative aluminum panels and aluminum-plastic composite panels;
[0005] 3. Industrial applications including the materials, design, and engineering of furniture panel glass and kitchen / bathroom panel glass, including microcrystalline glass, specialty cylindrical glass, and specialty cloned natural stone.
[0006] 4. Including industrial applications of electronic glass cover glass for mobile phones, automotive electronic glass, tablet electronic glass, laptop electronic glass, OLED display glass, aerospace and marine display glass, and foldable screen glass;
[0007] 5. Including industrial applications in LCD display glass.
[0008] 6. Including industrial applications in automotive glass, bulletproof glass, anti-theft and anti-robbery glass, aerospace and marine glass, and fire-resistant architectural glass;
[0009] 7. Industrial applications including the materials, design, and engineering construction of interior and exterior walls, floors, halls, and doors in wooden villas and mid- to high-end cement-structured villas.
[0010] 8. Including industrial applications of glass fiber. Background Technology
[0011] This invention discloses a glass application with atomically precise network structure manufacturing characteristics, low forming zone temperature, and high fracture toughness. It addresses a different technical problem and discloses different technical features compared to the closest existing technology. While this invention has some negative effects compared to the prior art [1] and [2] in certain aspects, it has significantly positive technical effects in other aspects.
[0012] The technical features disclosed in this invention are also different from the background technology [1] and [2] and all prior art.
[0013] Background Art [1]: Soda-lime glass and some prior art. Background Art [2]: Authorization Announcement No. CN103232160B Authorization Announcement Date 2018.07.24 Invention Title - A flat glass with a low coefficient of thermal expansion and its manufacturing process, etc. Background Art [3]: Authorization Announcement No. CN104193165B, Authorization Announcement Date 2017.10.17 Invention Title - Application of a composition in a flat glass with high strength and low hardness characteristics that is environmentally friendly and energy-saving and emission-reducing.
[0014] Background technology [I]. And various prior background technologies [2], and all prior technologies have not been fully revealed:
[0015] This invention discloses a glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness. The chemical composition of this glass material, calculated by weight percentage, includes: 0-12.9% aluminum oxide, 30-70% silicon oxide, 3-20% calcium oxide, 3-20% magnesium oxide, 0-15% boron oxide, 0-4% zirconium, and 0-20% sodium oxide. The silicon oxide content is 0.8 to 6 times that of calcium oxide, and the calcium oxide content is 0.3 to 2.5 times that of magnesium oxide. The viscosity range of the glass melt entering the forming operation zone is (4.25-5.57) log P, corresponding to a temperature of 650℃-1160℃.
[0016] For example, the technical features disclosed in this invention, using the crystallization temperature of the gradient furnace crystallization experiment, are between 1160℃ and 650℃, which is significantly lower than the forming viscosity temperature of the glass melt entering the (2.8)log P logarithm, revealing the special glass material characteristics of the glass melt of this invention that do not produce crystallization.
[0017] For example, the technical features disclosed in this invention, using a temperature-controlled atmosphere furnace for testing, or a glass high-temperature viscosity tester under conditions where the platinum rotor is stopped, revealed that the glass melt does not produce crystallization in the process stage region from the forming viscosity temperature of (2.8)log P to the temperature of the forming operation zone of the glass melt. The viscosity range in this process stage is (4.25-5.57)log P. The glass melt has been in this process for a period of not less than 60 minutes.
[0018] For the first time in history, it has been proven that the technical solution claimed in this invention produces a high-alumina glass with 12-22% alumina, while also containing 15-18% potassium and sodium (alkali) glass. During the melting stage, the viscosity-temperature logarithm (1.5)log P is approximately 1700°C. The viscosity-temperature logarithm (2.0)log P after degassing is approximately 1600°C. In contrast, the alumina content of this invention is 0-12.9%, and the sodium oxide content is 0-2%, 2.1-4%, or 4.1-6%. The viscosity-temperature logarithm (2.0)log P of the glass material of this invention is approximately 1440-1340°C after degassing; significantly lower than the traditional high-alumina glass with 12-22% alumina, which reaches only about 200°C.
[0019] Therefore, this invention overcomes and solves the historical technical problem that has plagued production, as proposed by traditional prior art theories, namely, the product's material properties are short, making it prone to crystallization and unable to be produced normally. This problem has been a long-standing challenge that people have been trying to solve but have not been able to.
[0020] This invention overcomes the difficulties that people with traditional processes dare not attempt to produce on the production line, resulting in unexpected technical effects.
[0021] One of the unexpected technical effects of this invention is that it enables the glass material of this invention, with an alumina content of 0-12.9% and a sodium oxide content of 0-2%, 2.1-4%, or 4.1-6%, to be safely mass-produced without causing glass crystallization and disrupting the production line, thanks to the protection of its novel technical properties. This has resulted in an unexpected technical effect.
[0022] The second unexpected technical effect of this invention is that it enables safe mass production without disrupting the production line due to glass crystallization. It also makes it possible to produce glass with lower viscosity properties, resulting in significant energy savings, thus creating another unexpected technical effect.
[0023] The third unexpected technical effect of this invention is that the glass material can form a three-dimensional network structure with atomic-level ultra-precision manufacturing characteristics, which can produce a fracture toughness of 0.5-1.0 (MPa*m1 / 2) and an elastic modulus of 80-95 Gpa.
[0024] The fourth unexpected technical effect of this invention is that it produces significantly greater energy savings and emission reductions than prior art. This will help to change the history of traditional glass heating, which relied solely on natural gas, and instead create a new era of energy saving, where heating the glass from within using electricity doubles the energy efficiency.
[0025] Therefore, this invention can utilize the newly discovered and verifiable novel properties of the material described above, which prevent crystallization, to produce unexpected technical effects:
[0026] This invention can change and eliminate the need for traditional high-alumina glass (containing alkali) in terms of production process equipment and thermal raw materials. Traditional high-alumina glass melting and bubble removal processes involve excessively high viscosity and temperatures, necessitating the use of natural gas as fuel. This invention allows for the use of an electric furnace process. This results in unexpected large-scale energy savings for the glass industry.
[0027] As professionals know, the thermal energy utilization rate of a fully electric furnace system is 80%, while that of a natural gas furnace system is only 40%.
[0028] Furthermore, as professionals know, in glass production, increasing the temperature from 1400 degrees Celsius to 1500 degrees Celsius generally increases energy consumption by about 20%-30%. This is because in this temperature range, the viscosity of the molten glass decreases further, requiring more heat to maintain the temperature and ensure the uniformity of the glass. Simultaneously, heat losses, such as those from the furnace, also increase significantly. From 1500 degrees Celsius to 1600 degrees Celsius, energy consumption typically increases by 30%-40%. As the temperature continues to rise, the heat demand of the molten glass increases exponentially. Moreover, at high temperatures, heat losses from the furnace's refractory materials and thermal radiation increase dramatically. Additionally, to ensure glass quality, the precision required for temperature control is higher, which also leads to a substantial increase in energy consumption.
[0029] The process was changed to using electric melting furnaces. This resulted in unexpected technological benefits, such as large-scale energy savings in the glass industry.
[0030] A forming process for a glass material with low crystallization strength, short material properties, high elastic modulus, high fracture toughness, and low forming zone temperature includes, but is not limited to, float forming, calendering, casting, overflow drawing, overflow forming, and tube drawing.
[0031] This invention discloses a novel, previously undisclosed, quantitative testing method for obtaining data on the length and intensity of glass material properties. It further explains how this method can be used to obtain data on the length and intensity of glass material properties and whether they affect crystal formation during glass production.
[0032] Because in the float glass process, the glass ribbon enters the tin bath, and during the leveling and polishing stages, the viscosity logarithm of this area is (2.7-3.2) log P for about 6 minutes. Then, the glass ribbon is pulled by about 20 pairs of edge-pulling machines to a thickness of 0.3-0.5 mm, which is approximately 6 minutes, until the viscosity logarithm of this area is (4.2-5.75) log P. At this point, the glass ribbon is nearly hardened and will not crystallize, and it will leave the tin bath, which takes about 6 minutes. The total time is approximately 18 minutes.
[0033] This invention employs a quantitative testing method, focusing not on the glass crystallization point temperature, but more importantly on the glass products of this invention, which have low crystallization strength and short crystallization time. A quantifiable testing method is used to quantitatively test the time from when the molten glass enters the forming process to when the molten glass hardens and no longer crystallizes, obtaining data on the length of the glass's crystallization properties and whether this affects the formation of crystals in the glass product during production.
[0034] Example 2. The present invention employs a quantitative testing method, Example 1:
[0035] We used a glass experimental atmosphere furnace with precise temperature control. The glass raw material of this invention was placed in a dry crucible for testing, melted, and then cooled after reaching 1400 degrees Celsius. Next, the temperature was controlled to maintain the glass at a viscosity logarithm of (2.7-3.2) log P, then at (4.2-5.75) log P, and finally at (5.75-10) log P, for a total time exceeding 60 minutes before removal. The requirement was that the melted glass in the experimental dry crucible should not exhibit crystallization after removal. This means that even with a time exceeding three times the approximately 18 minutes required for the glass to enter the tin bath and harden during glass production (60 minutes), crystallization should not occur.
[0036] Regarding our use of a high-temperature glass viscosity tester: Why, during the test using a high-temperature glass viscosity tester, does the rotation of the platinum rotor need to be stopped when the molten glass reaches the (2.0)log P logarithmic viscosity temperature stage (where the glass reaches the bubble-removing viscosity)?
[0037] When making the glass product of this invention, a high-temperature viscometer is used to test the viscosity and temperature of the glass. Because the viscosity of the glass is low in the high-temperature zone, the platinum rotor has to rotate once every 2-3 minutes in a very small dry crucible in glass melt that is hundreds of thousands of times less than the production conditions, which will generate a high proportion of friction on the glass melt.
[0038] According to the principles of crystallization conditions in glass technology, a high proportion of friction caused by the continuous rotation of molten glass makes it easier for alumina in the molten glass to transform into seed crystals, increasing the intensity of glass crystallization and causing problems such as grain growth and glass devitrification.
[0039] In the stage of viscosity logarithm (1.5)-(3.0-5.5)log P, if the high temperature viscometer rotates at 2 degrees per minute for about 3-4 hours during a long process, it is easy to increase the glass crystallization intensity. Alumina is easy to transform into crystal seed, which increases the glass crystallization intensity and produces grain growth and glass devitrification. This is different from the normal glass production process.
[0040] In the float glass process, during the glass ribbon leveling and polishing stages: the viscosity logarithm of this zone is (2.7-3.2) log P. The glass ribbon enters the tin bath and is pulled out after cooling – the viscosity logarithm of this zone is (5.75-7) log P. This takes approximately 12-15 minutes. Unlike high-temperature viscometers, which, due to the low viscosity of glass in the high-temperature zone, require the platinum rotor to rotate once every 2-3 minutes in a small volume of molten glass in a dry crucible, resulting in high friction against the molten glass, the platinum rotor cannot rotate for 3-4 hours in a small volume of molten glass. This friction easily increases the glass crystallization intensity, and alumina easily transforms into seed crystals, further increasing the glass crystallization intensity and leading to grain growth and glass devitrification.
[0041] Therefore, this invention discloses a glass application invention with atomic-level precision network structure manufacturing characteristics, low forming zone temperature, and high fracture toughness: it reveals a previously undisclosed material property of glass products, where the crystallization temperature in the gradient furnace crystallization experiment is between 1160℃ and 650℃, which is significantly lower than the forming viscosity temperature of the molten glass entering the (2.8)log P logarithm. Therefore, it will not produce crystallization before the molten glass enters the tin bath in processes such as float glass. This invention reveals a novel glass product that has never been previously disclosed. A quantitative testing method was employed, using a high-temperature glass viscosity tester under specific conditions: 1. The glass melt reaches a forming viscosity temperature of (2.8) log P; 2. The glass melt enters the forming operation zone, where the viscosity range is (4.25-5.57) log P; 3. The glass melt reaches a viscosity temperature where the viscosity log is (5.75-8) log P, indicating the glass is nearly hardened and will not crystallize. After at least 60 minutes, the glass does not crystallize. Even when the glass melt remains crystallized for 3 times longer than normal production conditions, or for 6-9 times longer (120-180 minutes), this invention demonstrates that this high-tech product, characterized by low crystallization intensity and short production time, solves the historical technical problem of short production time, which has long plagued production due to crystallization and difficulty in normal manufacturing. (2)
[0043] The industrial revolution of the three-dimensional network structure of glass products manufactured at the atomic level:
[0044] Our innovation in glass materials stems from fundamental technological breakthroughs that transform the three-dimensional network structure of glass products manufactured at the atomic level, rather than simply introducing new glass materials. It involves innovative breakthroughs in hundreds of different sub-categories of glass product components and their varying physicochemical properties.
[0045] [I] In the three-dimensional network structure of atoms in glass product technology, alumina is a network intermediate oxide. This is due to the relationship between network generation and network externalities.
[0046] There are only two types of network structures in glass product technology: The first is a network structure where aluminum and silicon atoms are linked together by sharing one or two oxygen atoms; this is the strongest network structure in glass materials. The second is a network structure where silicon atoms are linked together by sharing one oxygen atom; this type is less strong and easily disrupted by the presence of alkaline components such as potassium or sodium in the glass. This significantly reduces the glass's properties, including fracture toughness, elastic modulus, microhardness, and abrasion resistance.
[0047] When the alumina content is less than 2%, the aluminum atoms in the flat glass are almost entirely in a 4-coordinated configuration, forming a structure where each aluminum atom is surrounded by four oxygen atoms.
[0048] Although the present invention has some negative effects compared to the prior art [1] and [2] in some aspects, it has significant positive technical effects in other aspects.
[0049] The technical features disclosed in this invention are also different from the background technology [1] and [2] and all prior art.
[0050] The technical features of this invention are also different from those of the background technologies [1] and [2]. It utilizes a newly discovered quantitative testing method for glass applications with atomic-level precision network structure manufacturing features, low forming zone temperature, and high fracture toughness to obtain data on the long and short properties of glass materials. The technical problems solved in glass product applications are also different from those of the background technologies [1] and [2]. Summary of the Invention
[0051] 1. A glass application characterized by an atomically precise network structure, low forming zone temperature, and high fracture toughness, wherein the chemical composition of the glass material, by weight percentage, includes: 0-12.9% alumina, 30-70% silicon dioxide, 3-20% calcium oxide, 3-20% magnesium oxide, 0-15% boron oxide, 0-4% zirconium, and 0-20% sodium oxide, wherein the content of silicon dioxide is 0.8 to 6 times that of calcium oxide, the content of calcium oxide is 0.3 to 2.5 times that of magnesium oxide, and the viscosity range of the glass melt entering the forming operation zone is (4.25-5.57) log P, corresponding to a temperature of 650℃-1160℃.
[0052] The glass material can form a three-dimensional network structure with atomic-level ultra-precision manufacturing characteristics, and can produce a fracture toughness of 0.5-1.0 (MPa*m1 / 2) and an elastic modulus of 80-95 Gpa.
[0053] The viscosity-temperature logarithm of the glass material is approximately 1440-1340℃ (2.0 log P); the crystallization temperature of the gradient furnace crystallization experiment is between 1160℃ and 650℃, which is significantly lower than the forming viscosity temperature of the glass melt entering the (2.8 log P) logarithm.
[0054] Using a temperature-controlled atmosphere furnace or a glass high-temperature viscosity tester with the platinum rotor stopped, the glass melt enters the forming viscosity temperature range of (2.8)log P and then enters the forming operation zone. The viscosity temperature range of this zone is (4.25-5.57)log P. If the glass melt passes through this process zone for at least 60 minutes, the glass melt will not exhibit any special glass material characteristics such as crystallization.
[0055] A glass application with atomically precise network structure manufacturing characteristics, low forming zone temperature and high fracture toughness includes: a boron oxide content of 1-15%, a viscosity temperature logarithm of (1.5)log P of approximately 1400-1540℃ during the glass melting stage, and a glass viscosity temperature logarithm of (2.0)log P of approximately 1440-1340℃ after degassing.
[0056] A glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness includes an alumina content of 0-5%, 5.1-8%, or 8.1-12.9%.
[0057] A glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness includes a sodium oxide content of 0-2%, 2.1-4%, or 4.1-6%.
[0058] A glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness includes applications that omit natural gas as the heating material for glass melting and employ all-electric melting heating; and applications that omit the all-oxygen combustion process and reduce costs and save energy.
[0059] A glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness:
[0060] (a) Including industrial applications of architectural glass;
[0061] (b) Including industrial applications of special high-strength colored glaze glass and composite materials; including industrial applications of wall and floor colored glaze decorative glass made of special high-strength cloned natural stone; including industrial applications of special colored glaze glass decorative aluminum panels and aluminum-plastic composite glass composite materials; including industrial applications of integrated exterior wall insulation materials.
[0062] (c) Includes industrial applications of microcrystalline glass; includes industrial applications of cylindrical colored glaze glass decorative composites of special high-strength cloned natural stone; includes industrial applications of furniture panel composites and kitchen and bathroom panel colored glaze glass composites of special high-strength cloned natural stone.
[0063] (d) Includes industrial applications of electronic glass; includes industrial applications of cover glass for mobile phones, automotive electronic glass, tablet electronic glass, and laptop electronic glass; includes industrial applications of OLED display glass; includes industrial applications of foldable screen glass.
[0064] (e) Includes industrial applications of liquid crystal display glass, including industrial applications of aerospace and marine display glass; including industrial applications of boron-free and aluminum-free glass; including applications of boron-free and aluminum-free glass in the nuclear energy industry;
[0065] (f) Includes applications in automotive glass; includes applications in anti-theft and anti-robbery glass; includes applications in bulletproof glass; includes applications in high-rise marine glass; includes applications in aerospace glass; includes applications in fire-resistant glass;
[0066] (g) Includes the industrial application of special high-strength colored glaze glass and composite materials in the design and engineering construction of exterior walls, interior walls, floors, halls, and gates of wooden villas and mid-to-high-end cement structure villas.
[0067] A glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness includes: The invention newly discovers a novel property of the three-dimensional network structure in atomically manufactured glass products; in glass fiber applications, the glass melt of the invention, when entering a viscosity logarithmic range of (2.5-2.7)log P, corresponds to a temperature of 1520℃-1230℃; the glass melt of the invention's technical solution, when the crystallization temperature is higher than or lower than the glass forming temperature, after passing through the drawing holes in the drawing disc, ensures that the daily number of glass fiber filaments produced is greater than 95% of the number of drawing holes; and it possesses new material filamentation properties with high levels of ultra-high alumina glass fiber.
[0068] Applications of glass fiber in electronic applications; applications of glass fiber in aerospace, marine and low-altitude economic applications; applications of glass fiber in automotive applications; applications of glass fiber in wind turbine blades; applications of glass fiber in hydrogen energy storage devices or gaseous hydrogen storage devices; applications of glass fiber in special cement.
[0069] The present invention relates to the application of glass fiber and metal composite materials in components and shells of vehicles, ships, and aircraft;
[0070] The fracture toughness of this invention is 0.5-1.0 (MPa*m1 / 2), and the elastic modulus is 80-95 Gpa; the viscosity-temperature logarithm of the glass melting stage is approximately 1400-1540℃ (1.5)log P; the viscosity-temperature logarithm of the glass after degassing (2.0)log P is approximately 1440-1340℃.
[0071] A glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness; including but not limited to float glass forming, calendering forming, casting forming, overflow down-draw forming, overflow forming, and tube drawing forming. Attached Figure Description
[0072] Figure 1 This is a schematic diagram of a spatial network structure formed by silicon-oxygen tetrahedra sharing oxygen atoms at their vertices;
[0073] Figure 2 This is a schematic diagram of a spatial network structure formed by aluminum-oxygen tetrahedra through the sharing of oxygen atoms at the vertices;
[0074] Figure 3 This is a schematic diagram of the octahedral structure of an aluminum atom surrounded by eight oxygen atoms.
[0075] Figure 4 This is a schematic diagram of the tetrahedral structure of the four atoms surrounding a silicon atom;
[0076] Figure 5This is a schematic diagram of the production equipment used in the application of the glass of this invention, which features a manufacturing characteristic of atomic-level precision network structure, low forming zone temperature, and special glass material properties. Detailed Implementation
[0077] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0078] Example 1:
[0079] A glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness addresses a different technical problem than the closest existing technology. The disclosed technical features also differ.
[0080] A glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness, wherein the chemical composition of the glass material, by weight percentage, includes: 8.1-12.9% aluminum oxide, 30-70% silicon oxide, 3-20% calcium oxide, 3-20% magnesium oxide, 0-15% boron oxide, 0-4% zirconium, and 0-2% sodium oxide, wherein the content of silicon oxide is 0.8 to 6 times that of calcium oxide, and the content of calcium oxide is 0.3 to 2.5 times that of magnesium oxide. The viscosity range of the glass melt entering the forming operation zone is (4.25-5.57) log P, corresponding to a temperature of 650℃-1160℃.
[0081] This invention discloses—that no one has previously disclosed—a novel material property: using a precisely temperature-controlled atmosphere furnace, or a glass high-temperature viscosity tester with the platinum rotor stopped, to test the viscosity range (4.25-5.57) log P in the process stage from the forming viscosity temperature (2.8) log P to the temperature of the forming operation zone, where the glass melt passes through for at least 60 minutes, the glass melt does not exhibit crystallization. Therefore, crystallization does not occur before the glass melt enters the tin bath in processes such as float glass.
[0082] This invention discloses—something previously undisclosed—a novel property of the glass material: the (1.5)log P viscosity-temperature logarithm of the glass melting stage is approximately 1400-1540℃; the (2.0)log P viscosity-temperature logarithm of the glass degassing stage is approximately 1440-1340℃; and the crystallization temperature in the gradient furnace crystallization experiment is between 1160℃ and 650℃, significantly lower than the (2.8)log P logarithm of the forming viscosity temperature of the molten glass. Therefore, crystallization will not occur before the molten glass enters the tin bath in processes such as float glass.
[0083] This invention reveals—something no one has revealed before: the glass material can form a three-dimensional network structure with atomic-level ultra-precision manufacturing characteristics, resulting in a new material property with a fracture toughness of 0.5-1.0 (MPa*m1 / 2) and an elastic modulus of 80-95 Gpa.
[0084] A forming process for a glass material with low crystallization strength, short material properties, high elastic modulus, high fracture toughness, and low forming zone temperature includes, but is not limited to, float forming, calendering, casting, overflow drawing, overflow forming, and tube drawing.
[0085] In the embodiments, the application of a glass product with atomically precise network structure manufacturing characteristics includes, but is not limited to, the use of all-electric melting heating as the heating material for glass melting, omitting natural gas as the heating material; and the use of all-oxygen combustion processes, resulting in cost and energy savings. This can produce unexpected technical effects such as large-scale energy savings and significant cost reduction.
[0086] Example 2:
[0087] A glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness addresses a different technical problem than the closest existing technology. The disclosed technical features also differ.
[0088] A glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness, wherein the chemical composition of the glass material, by weight percentage, includes: 5.1-8% aluminum oxide, 30-70% silicon oxide, 3-20% calcium oxide, 3-20% magnesium oxide, 0-15% boron oxide, 0-4% zirconium, and 2.1-4% sodium oxide, wherein the content of silicon oxide is 0.8 to 6 times that of calcium oxide, and the content of calcium oxide is 0.3 to 2.5 times that of magnesium oxide. The viscosity range of the glass melt entering the forming operation zone is (4.25-5.57) log P, corresponding to a temperature of 650℃-1160℃.
[0089] The glass material can form a three-dimensional network structure with atomic-level ultra-precision manufacturing characteristics, which can produce a fracture toughness of 0.5-0.93 (MPa*m1 / 2) and an elastic modulus of 80-95 Gpa.
[0090] It reveals—something no one has revealed before: its features include: the use of all-electric melting heating as the heating material for glass melting, omitting natural gas as the heating material; and the use of all-oxygen combustion process, which reduces costs and saves energy.
[0091] This invention discloses—that no one has previously disclosed—a novel material property: using a precisely temperature-controlled atmosphere furnace, or a glass high-temperature viscosity tester with the platinum rotor stopped, to test the viscosity range (4.25-5.57) log P in the process stage from the forming viscosity temperature (2.8) log P to the temperature of the forming operation zone, where the glass melt passes through for at least 60 minutes, the glass melt does not exhibit crystallization. Therefore, crystallization does not occur before the glass melt enters the tin bath in processes such as float glass.
[0092] This invention discloses—that no one has previously disclosed—a novel material property: the (1.5)logP viscosity-temperature logarithm of the glass melting stage is approximately 1400-1540℃; the (2.0)logP viscosity-temperature logarithm of the glass degassing stage is approximately 1440-1340℃; and the crystallization temperature in the gradient furnace crystallization experiment is between 1160℃ and 650℃, significantly lower than the (2.8)logP logarithm of the forming viscosity temperature of the molten glass. Therefore, crystallization will not occur before the molten glass enters the tin bath in processes such as float glass.
[0093] The glass material, which has low crystallization strength, short material properties, high elastic modulus, high fracture toughness, and low forming zone temperature, is formed in a process including but not limited to float glass forming, calendering forming, casting forming, overflow drawing forming, overflow forming, and tube drawing forming.
[0094] In the embodiments, the application of a glass product with atomically precise network structure manufacturing characteristics includes, but is not limited to, the use of all-electric melting heating as the heating material for glass melting, omitting natural gas as the heating material; and the use of all-oxygen combustion processes, resulting in cost and energy savings. This can produce unexpected technical effects such as large-scale energy savings and significant cost reduction.
[0095] Example 3:
[0096] A glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness addresses a different technical problem than the closest existing technology. The disclosed technical features also differ.
[0097] A glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness, wherein the chemical composition of the glass material, by weight percentage, includes: 0-5% aluminum oxide, 30-70% silicon oxide, 3-20% calcium oxide, 3-20% magnesium oxide, 0-15% boron oxide, 0-4% zirconium, and 4.1-6% sodium oxide, wherein the content of silicon oxide is 0.8 to 6 times that of calcium oxide, and the content of calcium oxide is 0.3 to 2.5 times that of magnesium oxide. The viscosity range of the glass melt entering the forming operation zone is (4.25-5.57) log P, corresponding to a temperature of 650℃-1160℃.
[0098] The glass material can form a three-dimensional network structure with atomic-level ultra-precision manufacturing characteristics, and can produce a fracture toughness of 0.5-1.0 (MPa*m1 / 2) and an elastic modulus of 80-95 Gpa.
[0099] It reveals—something no one has revealed before: its features include: the use of all-electric melting heating as the heating material for glass melting, omitting natural gas as the heating material; and the use of all-oxygen combustion process, which reduces costs and saves energy.
[0100] This invention discloses—that no one has previously disclosed—a novel material property: using a precisely temperature-controlled atmosphere furnace, or a glass high-temperature viscosity tester with the platinum rotor stopped, to test the viscosity range (4.25-5.57) log P in the process stage from the forming viscosity temperature (2.8) log P to the temperature of the forming operation zone, where the glass melt passes through for at least 60 minutes, the glass melt does not exhibit crystallization. Therefore, crystallization does not occur before the glass melt enters the tin bath in processes such as float glass.
[0101] This invention discloses—that no one has previously disclosed—a novel material property: the (1.5)logP viscosity-temperature logarithm of the glass melting stage is approximately 1400-1540℃; the (2.0)logP viscosity-temperature logarithm of the glass degassing stage is approximately 1440-1340℃; and the crystallization temperature in the gradient furnace crystallization experiment is between 1160℃ and 650℃, significantly lower than the (2.8)logP logarithm of the forming viscosity temperature of the molten glass. Therefore, crystallization will not occur before the molten glass enters the tin bath in processes such as float glass.
[0102] The glass material can form a three-dimensional network structure with atomic-level ultra-precision manufacturing characteristics, which can produce new material properties with a fracture toughness of 0.5-0.8 (MPa*m1 / 2) and an elastic modulus of 70-85 Gpa.
[0103] A forming process for a glass material with low crystallization strength, short material properties, high elastic modulus, high fracture toughness, and low forming zone temperature includes, but is not limited to, float forming, calendering, casting, overflow drawing, overflow forming, and tube drawing.
[0104] In the embodiments, the application of a glass product with atomically precise network structure manufacturing characteristics includes, but is not limited to, the use of all-electric melting heating as the heating material for glass melting, omitting natural gas as the heating material; and the use of all-oxygen combustion processes, resulting in cost and energy savings. This can produce unexpected technical effects such as large-scale energy savings and significant cost reduction.
[0105] Example 4:
[0106] A glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness addresses a different technical problem than the closest existing technology. The disclosed technical features also differ.
[0107] (a) Including industrial applications of architectural glass;
[0108] (b) Including industrial applications of special high-strength colored glaze glass and composite materials; including industrial applications of wall and floor colored glaze decorative glass made of special high-strength cloned natural stone; including industrial applications of special colored glaze glass decorative aluminum panels and aluminum-plastic composite glass composite materials; including industrial applications of integrated exterior wall insulation materials.
[0109] (c) Includes industrial applications of microcrystalline glass; includes industrial applications of cylindrical colored glaze glass decorative composites of special high-strength cloned natural stone; includes industrial applications of furniture panel composites and kitchen and bathroom panel colored glaze glass composites of special high-strength cloned natural stone.
[0110] (d) Includes industrial applications of electronic glass; includes industrial applications of cover glass for mobile phones, automotive electronic glass, tablet electronic glass, and laptop electronic glass; includes industrial applications of OLED display glass; includes industrial applications of foldable screen glass.
[0111] (e) Includes industrial applications of liquid crystal display glass, including industrial applications of aerospace and marine display glass; including industrial applications of boron-free and aluminum-free glass; including applications of boron-free and aluminum-free glass in the nuclear energy industry;
[0112] (f) Includes applications in automotive glass; includes applications in anti-theft and anti-robbery glass; includes applications in bulletproof glass; includes applications in high-rise marine glass; includes applications in aerospace glass; includes applications in fire-resistant glass;
[0113] (g) Includes the industrial application of special high-strength colored glaze glass and composite materials in the design and engineering construction of exterior walls, interior walls, floors, halls, and gates of wooden villas and mid-to-high-end cement structure villas.
[0114] This embodiment presents a glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness. The technical problem it addresses differs from the closest existing technology. The disclosed technical features are also different.
[0115] The chemical composition of this glass material, calculated by weight percentage, includes: aluminum oxide content of 0-12.9%, silicon oxide content of 30-70%, calcium oxide content of 3-20%, magnesium oxide content of 3-20%, boron oxide content of 0-15%, zirconium content of 0-4%, and sodium oxide content of 0-20%. Among these, the content of silicon oxide is 0.8 to 6 times that of calcium oxide, and the content of calcium oxide is 0.3 to 2.5 times that of magnesium oxide. The viscosity range of the glass melt entering the forming operation zone is (4.25-5.57)log P, corresponding to a temperature of 650℃-1160℃.
[0116] The glass material can form a three-dimensional network structure with atomic-level ultra-precision manufacturing characteristics, which can produce a fracture toughness of 0.5-1.0 (MPa*m1 / 2) and an elastic modulus of 80-95 Gpa.
[0117] It reveals—something no one has revealed before: its features include: the use of all-electric melting heating as the heating material for glass melting, omitting natural gas as the heating material; and the use of all-oxygen combustion process, which reduces costs and saves energy.
[0118] In this embodiment, the test is conducted using an atmosphere furnace with precise temperature control, or a glass high-temperature viscosity tester with the platinum rotor stopped. In the process stage from the glass melt entering the forming viscosity temperature (2.8) log P to the temperature of the forming operation zone, the viscosity range in this zone is (4.25-5.57) log P. If the glass melt passes through this process stage for no less than 60 minutes, the glass melt will not exhibit any special glass material characteristics such as crystallization.
[0119] In this embodiment, the viscosity temperature logarithm of the glass melting stage (1.5)log P is approximately 1400-1540℃; the degassing viscosity temperature logarithm of the glass (2.0)log P is approximately 1440-1340℃; and the crystallization temperature of the gradient furnace crystallization experiment is between 1160℃ and 650℃, which is significantly lower than the forming viscosity temperature of the glass melt entering the (2.8)log P logarithm.
[0120] The alumina content is 0-5%, 5.1-8%, or 8.1-12.9%. The sodium oxide content is 0-2%, 2.1-4%, or 4.1-6%.
[0121] In this embodiment, a forming process for a glass material with low crystallization strength, short material properties, high elastic modulus, high fracture toughness, and low forming zone temperature includes, but is not limited to, float forming, calendering, casting, overflow drawing, overflow forming, and tube drawing forming processes.
[0122] In the embodiments, the application of a glass product with atomically precise network structure manufacturing characteristics includes, but is not limited to, the use of all-electric melting heating as the heating material for glass melting, omitting natural gas as the heating material; and the use of all-oxygen combustion processes, resulting in cost and energy savings. This can produce unexpected technical effects such as large-scale energy savings and significant cost reduction.
[0123] Example 5:
[0124] This embodiment presents a glass application featuring an atomically precise network structure, low forming zone temperature, and high fracture toughness. The technical problem it addresses differs from the closest existing technology. The disclosed technical features are also different.
[0125] The chemical composition of this glass material, by weight percentage, includes: 0-12.9% aluminum oxide, 30-70% silicon oxide, 3-20% calcium oxide, 3-20% magnesium oxide, 0-15% boron oxide, 0-4% zirconium, and 0-20% sodium oxide. The content of silicon oxide is 0.8 to 6 times that of calcium oxide, and the content of calcium oxide is 0.3 to 2.5 times that of magnesium oxide.
[0126] An application of a glass fiber product with an atomically precise network structure manufacturing feature includes: the invention newly discovers a new property of the three-dimensional network structure of the atomically manufactured glass product; in the application of glass fiber, the glass melt of the invention, when entering the viscosity logarithmic range of (2.5-2.7)log P, corresponds to a temperature of 1520℃-1230℃; the invention also discovers that the glass melt of the glass material of the invention, when the crystallization temperature is higher than the glass forming temperature or lower than the glass forming temperature, after passing through the drawing holes in the drawing disc, can produce a daily number of glass fiber filaments greater than 95% of the number of drawing holes; and it possesses the new material filament-forming properties of high-level ultra-high alumina glass fiber.
[0127] This includes applications of glass fiber in electronics; applications of glass fiber in aerospace, marine, and low-altitude economic applications; applications of glass fiber in automobiles; applications of glass fiber in wind turbine blades; applications of glass fiber in hydrogen energy storage devices or gaseous hydrogen storage devices; and applications of glass fiber in special cement.
[0128] This includes the application of the glass fiber and metal composite material of the present invention in components and shells of vehicles, ships and aircraft.
[0129] In applications of glass fiber, this invention can produce new material properties with a fracture toughness of 0.8-1.1 (MPa*m1 / 2) and an elastic modulus of 80-120 Gpa.
[0130] In the embodiments, the cerium oxide content may be 0.5%, 0.5-1%, 1-2%, or 2-9%.
[0131] In the embodiments, the glass fiber structure of the present invention, characterized by an atomic-level network structure, contains 0.3-6% zirconium. This zirconium undergoes a phase transition at high temperatures, creating stress within the three-dimensional space of the glass, thus increasing the elastic modulus of the glass. Furthermore, the 0.3-4% zirconium content contributes to a high level of thermal shock resistance, preventing cracking or breakage during rapid temperature changes. Finally, the 1-6% zirconium content, coupled with the fact that its diameter is larger than the wavelength of visible light, contributes to the opacity of the glass, allowing for various product applications.
[0132] In the embodiments, the cerium oxide content may be 0.5%, 0.5-1%, 1-2%, or 2-9%.
[0133] In the embodiments, the application of a glass product with atomically precise network structure manufacturing characteristics includes, but is not limited to, the use of all-electric melting heating as the heating material for glass melting, omitting natural gas as the heating material; and the use of all-oxygen combustion processes, resulting in cost and energy savings. This can produce unexpected technical effects such as large-scale energy savings and significant cost reduction.
[0134] In summary, the glass of this invention has a specific range of chemical compositions, and the disclosed technical features are different from those of the prior art. Although this invention has some negative effects compared to the prior art [1] and [2] in some aspects, it has significant positive technical effects in other aspects.
[0135] The present invention discloses a glass application with atomic-level precision network structure manufacturing characteristics, low forming zone temperature and high fracture toughness, as well as production equipment and production method; the technical features of the present invention are also different from the background technology; [1]. The glass of the present invention has a specific range of chemical composition, and the disclosed technical features are also different from the background technology, and the technical problems to be solved are also different; [2]. The present invention has newly discovered a new property of a glass application with atomic-level precision network structure manufacturing characteristics, low forming zone temperature and high fracture toughness, and a new property of a glass material with low forming zone temperature and special glass material characteristics. By utilizing the new properties, unexpected technical effects such as fracture toughness of 0.5-1.0 (MPa*m1 / 2) and elastic modulus of 80-95Gpa can be produced. [3]. The newly discovered glass melting stage viscosity temperature logarithm (1.5)log P is about 1400-1540℃; the glass viscosity temperature logarithm (2.0)log P degassing is about 1440-1340℃; the crystallization temperature of the gradient furnace crystallization experiment is between 1160℃ and 650℃, which is significantly lower than the glass product with a new property characteristic of glass products with a (2.8)log P logarithm forming viscosity temperature. [4]. The newly discovered glass product with a new property characteristic of glass products with a new property characteristic of glass products with a new property characteristic of glass products with a new property characteristic of glass products with a new property characteristic of glass products with a new property characteristic of glass products with a new property characteristic of glass products with a new property characteristic of glass products with a new property characteristic of glass products with a new property characteristic of glass products with a new property characteristic of glass products with a new property characteristic of glass products with a new property characteristic of glass products with a (2.8)log P logarithm forming viscosity temperature to a (4.25-5.57)log P viscosity temperature in the process stage where the glass liquid enters the forming operation zone temperature, and the glass liquid enters the forming operation zone temperature in the process stage where the viscosity range is (4.25-5.57)log P viscosity temperature in the process stage where the glass liquid enters the forming operation zone ... It can obtain quantifiable data on the length and shortness of glass properties, and can quantitatively test new property characteristics of glass products with low crystallization strength and short length.
[0136] The alkali-free glass products of this invention, which demonstrate the low forming zone temperature and special glass material characteristics, can overcome and solve the historical technical problem that has plagued the production of high-alumina glass products for a long time, as proposed by traditional prior art theories. This problem stems from the short material properties of the products, which make them prone to crystallization and thus unable to be produced normally.
[0137] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A glass application characterized by an atomically precise network structure manufacturing feature, low forming zone temperature, and high fracture toughness, characterized in that: The chemical composition of this glass material, calculated by weight percentage, includes: aluminum oxide content of 0-12.9%, silicon oxide content of 30-70%, calcium oxide content of 3-20%, magnesium oxide content of 3-20%, boron oxide content of 0-15%, zirconium content of 0-4%, and sodium oxide content of 0-20%. Among these, the content of silicon oxide is 0.8 to 6 times that of calcium oxide, and the content of calcium oxide is 0.3 to 2.5 times that of magnesium oxide. The viscosity range of the glass melt entering the forming operation zone is (4.25-5.57)log P, corresponding to a temperature of 650℃-1160℃. The glass material can form a three-dimensional network structure with atomic-level ultra-precision manufacturing characteristics, and can produce a fracture toughness of 0.5-1.0 (MPa*m1 / 2) and an elastic modulus of 80-95 Gpa. The viscosity-temperature logarithm of the glass material is approximately 1440-1340℃ (2.0 log P); the crystallization temperature of the gradient furnace crystallization experiment is between 1160℃ and 650℃, which is significantly lower than the forming viscosity temperature of the glass melt entering the (2.8 log P) logarithm. Using a temperature-controlled atmosphere furnace or a glass high-temperature viscosity tester with the platinum rotor stopped, the glass melt enters the forming viscosity temperature range of (2.8)log P and then enters the forming operation zone. The viscosity temperature range of this zone is (4.25-5.57)log P. If the glass melt passes through this process zone for at least 60 minutes, the glass melt will not exhibit any special glass material characteristics such as crystallization.
2. The glass application according to claim 1, characterized by its atomically precise network structure manufacturing features, low forming zone temperature, and high fracture toughness, is characterized in that... include: The boron oxide content is 1-15%, and the viscosity-temperature logarithm of the glass melting stage is approximately 1400-1540℃ (1.5)log P. The degassing value of the glass viscosity logarithm at temperature (2.0) is approximately 1440-1340℃.
3. The glass application according to claim 1, characterized by its atomically precise network structure manufacturing features, low forming zone temperature, and high fracture toughness, is characterized by comprising: The alumina content is 0-5%, 5.1-8%, or 8.1-12.9%.
4. The glass application according to claim 1, characterized by its atomically precise network structure manufacturing features, low forming zone temperature, and high fracture toughness, is characterized in that... include: The sodium oxide content is 0-2%, 2.1-4%, or 4.1-6%.
5. The glass application according to claim 1, characterized by its atomically precise network structure manufacturing features, low forming zone temperature, and high fracture toughness, is characterized in that: This includes applications that omit natural gas as the heating material for glass melting and instead use all-electric melting heating as the heating material for glass melting; This includes applications that omit the oxy-fuel combustion process and reduce costs and save energy.
6. The glass application according to claim 1, characterized by its atomically precise network structure manufacturing features, low forming zone temperature, and high fracture toughness, is characterized in that: (a) Including industrial applications of architectural glass; (b) Including industrial applications of special high-strength colored glaze glass and composite materials; including industrial applications of colored glaze decorative glass for walls and floors made of special high-strength cloned natural stone; including industrial applications of special colored glaze glass decorative aluminum plates and aluminum-plastic composite glass composite materials. This includes the industrial application of integrated exterior wall insulation panels; (c) Includes industrial applications of microcrystalline glass; includes industrial applications of cylindrical colored glaze glass decorative composites of special high-strength cloned natural stone; includes industrial applications of furniture panel composites and kitchen and bathroom panel colored glaze glass composites of special high-strength cloned natural stone. (d) Including industrial applications of electronic glass; This includes industrial applications of cover glass for mobile phones, automotive electronics, tablets, and laptops. Including industrial applications of OLED display glass; Including industrial applications of foldable screen glass; (e) Including industrial applications of liquid crystal display glass, including industrial applications of aerospace and marine display glass; Including industrial applications of boron-free and aluminum-free glass; Including applications in the nuclear energy industry using boron-free and aluminum-free glass; (f) Includes applications in automotive glass; includes applications in anti-theft and anti-robbery glass; includes applications in bulletproof glass; includes applications in high-rise marine glass; includes applications in aerospace glass; includes applications in fire-resistant glass; (g) Includes the industrial application of special high-strength colored glaze glass and composite materials in the design and engineering construction of exterior walls, interior walls, floors, halls, and gates of wooden villas and mid-to-high-end cement structure villas.
7. The glass application according to claim 1, characterized by its atomically precise network structure manufacturing features, low forming zone temperature, and high fracture toughness, is characterized in that... include: The present invention has newly discovered a novel property of the three-dimensional network structure of glass products manufactured at the atomic level. In the application of glass fibers, the glass melt of the present invention, when entering the viscosity logarithmic range of (2.5-2.7)log P, corresponds to a temperature of 1520℃-1230℃. The present invention also discovered that the glass melt of the glass material of the present invention, when the crystallization temperature is higher than the glass forming temperature or lower than the glass forming temperature, after passing through the drawing holes in the drawing disc, can produce a daily number of glass fiber filaments that are greater than 95% of the number of drawing holes; it can possess the new material filament-forming properties of ultra-high alumina glass fiber with a high level of sophistication. Applications of glass fiber in electronic applications; applications of glass fiber in aerospace, marine and low-altitude economic applications; applications of glass fiber in automotive applications; applications of glass fiber in wind turbine blades; applications of glass fiber in hydrogen energy storage devices or gaseous hydrogen storage devices; applications of glass fiber in special cement. The present invention relates to the application of glass fiber and metal composite materials in components and shells of vehicles, ships, and aircraft; The fracture toughness of this invention is 0.5-1.0 (MPa*m1 / 2), and the elastic modulus is 80-95 Gpa; the viscosity-temperature logarithm of the glass melting stage is approximately 1400-1540℃ (1.5)log P; and the viscosity-temperature logarithm of the glass after degassing (2.0)log P is approximately 1440-1340℃.
8. The glass application according to claim 1, characterized by its atomically precise network structure manufacturing features, low forming zone temperature, and high fracture toughness; characterized in that: Including but not limited to float forming process, calendering forming process, casting forming process, overflow down-draw forming process, overflow forming process, and tube drawing forming process.
Citation Information
Patent Citations
A kind of flat glass with low thermal expansion coefficient and its manufacturing process
CN103232160B
Application of a composition in flat glass with characteristics of environmental protection, energy conservation and emission reduction, high strength and low viscosity
CN104193165B